Picture guided learning - A picture-based clinical skill teaching resource in undergraduate nursing in South Australia - Ying Yu; Jodie Price; Vincent Pearson; Leeanne Pront; Angie Sterland; Maurine Redden; Fathimath Shifaza (International Journal of Advanced Health Science and Technology, 2021)
A competent nursing graduate is required to perform psychomotor skills related to clinical procedures, articulate knowledge to support their activities, work in a team with efficient time management skills and have strategies to perform in the increasingly busy clinical environment and with complex patient acuity. Student Evaluation of Teaching data from an undergraduate nursing clinical subject 2014-2018 identified an inconsistency in clinical skill teaching/delivery by educators which needed to be addressed. This study aimed to evaluate the outcome of implementing the Clinical Skill Storybook as an additional teaching resource for students’ clinical skill development. A descriptive analysis approach was applied to summarise quantitative and qualitative subject evaluation data along with Clinical Skill Storybook evaluation questionnaires (2018-2020). Data analysis identified five themes: (1) Clinical Skill Storybook as a Learning Resource, (2) Self-directed learning and peer support, (3) Developing clinical skill competency, (4) Preparation for clinical placement, and (5) Maintaining teaching consistency. It was evident that the Clinical Skill Storybook provided an easy-to-follow visual guide which assisted students’ confidence and competence of skill development. The subject evaluation highlights that students were significantly more satisfied with the teaching resources than in previous years. The implementation of the Clinical Skill Storybook actively improved students’ skill acquisition, confidence, and readiness for placement. The findings indicated that picture-based resources such as the Clinical Skill Storybook are beneficial for nursing students’ clinical skill development. Further involvement with stakeholders such as clinical venues in developing the clinical skill storybook is planned for future exploration.